ANALISIS ASPEK EKONOMI DAN SOSIAL KOTA PEKANBARU SEBAGAI KOTA LAYAK HUNI - Rio Sayang Juliandi; Mardiana; Dahlan Tampubolon (Revenue : Jurnal Ekonomi Pembangunan dan Ekonomi Islam, 2021)
To accelerate the development and quality of Pekanbaru City in the 2017-2022 period, the Pekanbaru City Government has a vision and mission of "Realizing a Civilian Smart City Pekanbaru". So there is a need for an analysis of livability in Pekabaru City through research on Economic and Social aspects. This study aims to determine the achievement of the concept of a liveable city in Pekanbaru City from the point of view of the economic and social aspects. This qualitative research was conducted by collecting questionnaire data to 60 respondents proportionally in Pekanbaru City. The analysis used is Gap analysis and Achievement Index analysis. The results of the index show that the achievement value in Pekanbaru City is 60.70. Based on the interpretation of the Liveliability Index results, Pekanbaru City gets good results. Among the indicators contained in the economic aspect that get the highest score is the indicator of the availability of goods and services for daily needs which are easily found in Pekanbaru City. The indicator on the economic aspect that has the lowest value is that local residents are guaranteed employment. This is due to the fact that several companies, especially in the industrial and mining sectors, employ workers from outside the city of Pekanbaru. While the indicators on the social aspect that get the highest score are the ease of public access and social tolerance in the people of Pekanbaru City. The indicator that gets the lowest score is Availability of Creative Space. From the data above, it can be seen that Sail District is the District with the highest achievement index compared to other districts. While Tampan is the district with the lowest achievement index. Tampan District with a population density in Pekanbaru City has a lower Achievement Index than other sub-districts, so it can be concluded that the denser an area is, the higher the indicator of community satisfaction with the livability of the area.